2016
DOI: 10.1016/bs.aivir.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Architecture of the Coronavirus Particle

Abstract: Coronavirus particles serve three fundamentally important functions in infection. The virion provides the means to deliver the viral genome across the plasma membrane of a host cell. The virion is also a means of escape for newly synthesized genomes. Lastly, the virion is a durable vessel that protects the genome on its journey between cells. This review summarizes the available X-ray crystallography, NMR, and cryoelectron microscopy structural data for coronavirus structural proteins, and looks at the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(127 citation statements)
references
References 170 publications
(199 reference statements)
4
120
1
1
Order By: Relevance
“…The fifth ORF encodes a 241 amino acid long three-pass transmembrane protein that resembles the coronavirus M protein, and the sixth ORF encodes a putative N protein of 459 amino acids. Together, these 3′-ORFs appear to encode a complete coronavirus functional repertoire, and are present in the same order found on all other currently known coronavirus genomes (Neuman and Buchmeier, 2016). The start codons of the putative S and M ORFs appear to overlap with the stop codons of preceding ORFs, indicating a relatively compact genome.…”
Section: Mlev Genomementioning
confidence: 66%
See 1 more Smart Citation
“…The fifth ORF encodes a 241 amino acid long three-pass transmembrane protein that resembles the coronavirus M protein, and the sixth ORF encodes a putative N protein of 459 amino acids. Together, these 3′-ORFs appear to encode a complete coronavirus functional repertoire, and are present in the same order found on all other currently known coronavirus genomes (Neuman and Buchmeier, 2016). The start codons of the putative S and M ORFs appear to overlap with the stop codons of preceding ORFs, indicating a relatively compact genome.…”
Section: Mlev Genomementioning
confidence: 66%
“…Lastly, the structural protein repertoire of nidoviruses appears to be quite broad compared to other known virus orders. There do not appear to be any conserved nidovirus structural proteins with the possible exception of the nucleoprotein (discussed elsewhere (Neuman and Buchmeier, 2016)), and even that homology can only be regarded as hypothetical until more structures of putative nucleoproteins are solved. A tentative categorization of nidovirus structural proteins, based on size, predicted transmembrane regions, and predicted protein secondary structure is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A) . The 3′‐proximal third encodes the structural and accessory proteins . These two polyproteins are processed into 15 or 16 mature Nsps to form the replication/transcription complex.…”
Section: Proteases Of Positive‐sense Single‐stranded Rna ((+)Ssrna) Vmentioning
confidence: 99%
“…During assembly of the authentic virion M interacts with itself, with the nucleocapsid protein N, with E and with the S protein [44,58,65]. M protein is present as a dimer in the virion and high resolution imaging has suggested that it presents as two conformations, long and compact (M LONG and M COMPACT ), which together induce membrane curvature as well as binding to the nucleocapsid [66,67].…”
Section: Structural Protein Interactionsmentioning
confidence: 99%